PENGARUH BENTUK TES DALAM MATA PELAJARAN SEJARAH - SUYUTI SUYUTI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2012)
The objective of the research is to find out the effect of the formative test form, learning style, and the students’ achievement in history by controlling the students’ reasoning capacity. Research data was collected by questionnaire and analyzed by using the Analysis of Covariate (ANACOVA). The research result after controlling the students’ reasoning capacity shows that: the students’achievement in history for group of students who was given the essay test is higher than that of the students which was given the multiple choice test, the students’ achievement in history for group of students who tended to apply lateral thinking style is higher than that of the students applying the vertikal thinking style, there is an interaction effect between the formative test and the thinking style on the students’ achievement in history, the students’ achievement in history for group of students who tended to apply the lateral thinking style and at the same time was given the essay test is higher than that of the students who were given the multiple choice test, the students’ achievement in history for group of students who tended to apply the vertikal thinking style and same time were given the essay test is lower than that of the students who were given the multiple choice test, and the students’ achievement in history for the students who applied the lateral thinking style and at the same time were given the essay test is higher than that of the students who applied the vertikal thinking style.